Kajian Sumbangan Teori Linguistik Ibnu Jinni ke Atas Perkembangan Linguistik Arab Moden - Sulaiman Bin Ismail (Universiti Sains Islam Malaysia, 2024)
This article mainly focuses on a discussion of the linguistic theories that had been introduced and discussed thoroughly by Ibnu Jinni at the beginning of the fourth century of al-Hijrah in which it witnessed the glorious era of knowledge development in the Abbasid Empire. Ibnu Jinni 5 influence and his personality had greatly given an enormous influence on the development of modern Arabic linguistic. His introductory theories had been used by many generations as their main references and sources to develop and expand many new theories in the study of Arabic. Thus, this article depicts his theories on the origin of language, the words derivation, vowel, consonant letters and phonemes in the morphological system of Arabic, sounds of the words that demonstrate the strength of meanings, the similarities of the words because of the similarities of the meanings and some other theories that had had great influence on the development of Arabic linguistic in general.